Progress in the Development of the Written Language of the Yine, Shipibo and Ashaninka People - Alonzo Sutta, Alicia (2010)
For the last two years, native speakers of Yine, Shipibo, and Ashaninka have decided to propose alphabets that represent their oral language in a written form, so educational materials for bilingual schools are made.